Effects of polystyrene microplastics on dechlorane plus bioaccumulation in the thick-shell mussel - Xu, Qiuxia; Peng, Xijian; Guo, Yuanming; Hao, Qing; Hou, Yanlin; Yang, Chenghu (Frontiers in Environmental Science, 2023)
The combined pollution of microplastics (MPs) and persistent organic pollutants (POPs) have attracted increasing attention from the international community in recent years. MPs can affect the toxicity, bioenrichment rate and bioavailability of POPs through adsorption and other interactions. Dechlorane Plus (DP) is a chlorinated flame retardant and a typical. DPs used mainly in various polymer materials, such as electrical wire and cable coating. The pollutions of MPs and DPs (syn and anti isomers, syn-DP [s-DP] and anti-DP [a-DP]) are ubiquitously present in the environment. However, the effect of MPs on the bioaccumulation of DP has not been reported. In this study, thick-shell mussels (Mytilus coruscus) were exposed to DPs (10 ng/L, DP10), DPs and polystyrene microplastics (PS) (10 ng/L DP +10 μg/L PS, DP10/PS10; 10 ng/LDP+20 μg/L PS, DP10/PS20) for 28 days to investigate the effect of MPs on DPs enrichment. Thick-shell mussels accumulated DPs in the adductor muscle, gill, and gonad showed an increasing trend with time, but the concentration of DPs in the visceral mass does not show a time-dependent manner. The concentration of DPs in the gonads and gills was significantly affected by the concentration of PS (p < 0.05), but there was no significant correlation between the concentration of DPs and the concentration of PS in the adductor muscle and visceral mass (p > 0.05). Moreover, DPs showed selective enrichment of syn-DP in thick-shell mussel tissues, and there was no significant correlation between this result and PS concentration (p > 0.05). These findings provide a new entry point for studying the interaction between microplastics and persistent organic pollutants in marine organisms.